Adolescents and HIV in Developing Countries: New Research Directions - MacPhail, Catherine (PINS-Psychology in Society, 2026)
Adolescents are of interest in HIV/STD studies as they are a group whose behaviour places them at increased risk of HIV infection (Hein, 1992). Adolescence is a period characterised by the development and formation of sexuality, a process which frequently involves a high turn-over of sexual partners (Krahe and Reiss, 1995; Lear, 1995). Teenage experimentation with drugs and alcohol frequently leads to the adoption of high risk behaviours or engagement in unplanned episodes of casual sex (Weatherburn and Project SIGMA, 1992). In addition, adolescents are particularly vulnerable to the normative social influences of their peers (DiClemente, 1990). These influences among adolescents tend to discourage the adoption of safe sexual behaviour by encouraging negative associations to be attached to condoms and their use. While the intense influence of nonnative social values on adolescents makes them increasingly vulnerable to HIV infection, if HIV-preventive behaviour can be made to seem the norm, teenagers may also be readily influenced by this (Fisher, Misovich & Fisher, 1992). Finally, aspects of teenagers’ lives are dominated by feelings of invulnerability which allow them to take the chances they see as developmentally important (Memon, 1991; Ingham, Woodcock and Stenner, 1992). While adolescents know about HIV, most have not personalised the threat of AIDS (Edgar et al, 1992). The factors which place adolescents at risk of HIV tend to stereotype adolescence as a period of traumatic social behaviour. While much of the literature has encouraged this stereotype, adolescence should not be viewed as a completely negative developmental stage (Aggleton, 1991).